ALTERNATIF PENANGULANGAN EROSI DI PANTAI LEBIH DENGAN KONSTRUKSI SUBMERGED BREAKWATER - I Kadek Suarnaya; Cok Agung Yujana; Nyoman Surayasa (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2018)
ABSTRACT Lebih beach every year have changed the shoreline, recorded in 2015 the erosion length along 0.478 km. Considering the current condition, it is necessary to make an alterfnatif planning of beach protection to reduce the erosion effect. Submerged breakwater by using dolos is one of alternative structure for beach protection. Dolos was selected to easy to get the required material weight because dolos is precast concrete. Result of analysis shown top elevation of breakwater is -1.050, width in the top of breakwater is 0.678 m. First layer of dolos weight is 93.2 kg, second layer of stone weight is 9.32 kg, the core layer of stone weight is 0.46 kg. Height of foundation is 0.814 m, width of foundation is 0.610 m and weight of stone in foundation is 24 kg. Bugget plan to construct submerged breakwater in Lebih Beach is IDR.4,501,404,000.00. Keywords: breakwater, erosion, Lebih beach